บทบาทของ "กลุ่ม 16" ในฐานะกลุ่มทางการเมือง - มีลาภ เปรมทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objectives of the study are to study on the establishment, form of relation structure, disintegration of the political faction as well as its activities which are related to public interest. The method of the study is based upon quality research. The data was collected from the selected politicians of "Group 16", university lecturers, police officers and journalists by in-depth interview and observation technique in order to test the hypothesis Group 16 is a faction within a political group that has equal status to other group members; its actual role is for economical and political interest rather than being a political interest group. The result of the study concludes that the establishment of Group 16 is based on personal relations among its members, both individually and family-ties. A notable characteristic of the group member is an indentical one: the organization and its management is based on compromise, seniority, liberty, fratunity which are conformed to the Thai political culture. As for the political role of the group; it is found out that the group has sufficient power to bargain with the political parties. Moreover, the group has influence on seeking for personal interest.